Fresno County Bar Association Law Day Luncheon with Keynote Speaker Justice Pauline Davis Hanson - Watkins, Howard::::::::: (1982)
Fresno County Bar Association President-elect Doug Jensen and Fresno County Young Lawyers President Harold Lai